Unlocking the relationship between destination brand value and tourists' intentions to visit: A case study in Quang Binh province - Chi, Nguyen Thi Phuong (Journal of Tourism Management Research, 2024)
This study aims to explore the factors that constitute the concept of destination brand value and analyze the influence of these elements on tourists' intention to choose a destination. The destination is seen as a brand that builds and maintains a unique venue image, enhances its competitive position and attracts visitors to this destination. Vietnam has much potential to attract tourists with its scenic landscapes and historical cultural relics. However, since COVID-19, attracting tourists has yet to be able to compete with other countries in the region such as Thailand, Singapore and the Philippines. How can Vietnamese destination brand value be improved to compete in attracting tourists? To answer the above research question, a quantitative approach was applied. Data was collected from 295 tourists intending to visit Quang Binh, a central province of Vietnam with many famous natural, cultural and historical attractions. Through exploratory factor analysis, research results show that three factors of brand value impact the online travel experience: destination image brand quality, destination brand awareness and destination brand image. This study confirms the positive relationship between online destination brand experience and destination intention to visit. Some implications are proposed for managers in the tourism industry to improve the competitive advantage of the Quang Binh destination brand.